PENGONTROLAN PARASIT SALURAN PENCERNAAN KAMBING PERANAKAN ETAWA MELALUI PENGGUNAAN SUPLEMEN PAKAN DAN HERBAL - Anie Insulistyowati; Darlis Darlis; Pudji Rahayu (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
This study aims to control the gastrointestinal helminth parasite of Peranakan Etawa (PE) goats through the use of herb and feed supplements. A total of 20 PE goats with an average body weight of 19.74 ± 4.21 kg were divided into 4 groups. This study used a Completely Randomized Block Design consisting of 4 groups and 4 treatments. The treatment given to goats was P0: without Urea Molasses Mineral Block (UMMB) supplements and anthelmintic, P1: UMMB 100 g (1 day), P2: Albendazole (1 day), P3: UMMB 100 g + Curcuma xanthorrhiza (3 days), P4: UMMB 100 g + Curcuma xanthorrhiza (7 days). The data collected were prevalence, type of gastrointestinal parasites, and egg count per gram (EPG) of feces. Examination of EPG using the Floatation method. The results of the study obtained the prevalence of helminth parasites 100%. The types of helminth parasites found are Strongyloides, Haemonchus, Bunostomus, Dicrocoelium, Avitellina, and Oesophagustomum. The EPG reduction in UMMB and UMMB+Curcuma xanthorrhiza treatment (3 days) was the highest at around 64.88%. It was concluded that all goats were infested with helminth parasites with a mild level of infestation (epg < 100). The types of helminth parasites found are Strongyloides, Haemonchus, Bunostomus, Dicrocoelium, Avitellina, and Oesophagustomum. The use of feed supplements and herbs can reduce helminth parasites infections in PE goats